Strategic Analysis of the Financing System of Iran Health Insurance Organization - Ali Mohammad Mosadeghrad; Mahdiyeh Heydari; Mahya Abbasi; Mahdi Abbasi (پیاورد سلامت)
Background and Aim: Health insurance organizations play an important role in increasing people’s access to health services and protecting them financially against catastrophic health costs. Iran Health Insurance Organization (IHIO) is one of the largest public health insurance organizations in Iran, which faces many challenges. The purpose of this research is the strategic analysis of health financing performance of IHIO. Materials and Methods: This qualitative research was conducted using interpretive phenomenology method through using semi-structured interviews with 25 managers and employees of IHIO. In addition, relevant documents and archival data of IHIO were collected and analyzed. Thematic analysis method was used to analyze the data. Results: Overall, 19 strengths, 24 weaknesses, 14 opportunities, 37 threats and 43 solutions were identified for the health financing system of IHIO. Increasing the coverage of health services, correcting the information databases of the insured and electronic prescribing were the most important strengths, and inappropriate pooling of financial resources, incomplete risk pooling, high administrative costs, and inefficient control were the most important weaknesses of IHIO. The most important opportunities for IHIO include the government’s support for universal health coverage and emphasis on primary health care, legal support for consolidating health insurance funds and improving the health technology assessment system in the country. The main threats to IHIO include political and economic unstability, low health insurance premiums, decisions without scientific support and insufficient enforcement of laws. Finally, solutions such as modernizing the tax system, increasing the health literacy of the community, reducing bureaucracy, increasing transparency and accountability, and reforming the monitoring and evaluation system were identified to strengthen the performance of the financing system of IHIO. Conclusion: Iran’s health insurance organization is facing numerous structural, contexual and process challenges that have reduced its productivity. Decrease in revenues, increase in costs and decrease in efficiency have caused problems in the financing performance of this organization. Recognizing the weaknesses and challenges of financing performance and applying corrective interventions is the first step in strengthening the sustainability of health financing of IHIO.